2012
DOI: 10.3402/dfa.v3i0.12236
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of Charcot neuroarthropathy: current concepts

Abstract: The pathogenesis of Charcot neuroarthropathy (CN) has been poorly understood by clinicians and scientists alike. Current researchers have made progress toward understanding the cause of CN and possible treatment options. The authors review the current literature on the pathogenesis of this debilitating disorder and attempt to explain the roles of inflammation, bone metabolism, and advanced glycation end products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…The literature pertaining to Charcot arthropathy has acknowledged this lack of validation, citing the subjectivity of the classification's stages and the difficulties encountered when attempting to distinguish the end of one stage and the beginning of the next as impediments to proper validation [6]. There are other challenges that complicate validation, including the limited prevalence of Charcot arthropathy, which is reported to be 0.08% to 7.5% in patients with diabetes, the high frequency of delayed and missed diagnoses, and the multitude of joints affected [14,15]. Additionally, validation requires assessment of each patient's imaging and physical examination findings by multiple observers at one time, and with time, which can be difficult to facilitate.…”
Section: Validationmentioning
confidence: 99%
“…The literature pertaining to Charcot arthropathy has acknowledged this lack of validation, citing the subjectivity of the classification's stages and the difficulties encountered when attempting to distinguish the end of one stage and the beginning of the next as impediments to proper validation [6]. There are other challenges that complicate validation, including the limited prevalence of Charcot arthropathy, which is reported to be 0.08% to 7.5% in patients with diabetes, the high frequency of delayed and missed diagnoses, and the multitude of joints affected [14,15]. Additionally, validation requires assessment of each patient's imaging and physical examination findings by multiple observers at one time, and with time, which can be difficult to facilitate.…”
Section: Validationmentioning
confidence: 99%
“…Proposed mechanisms via somatic and autonomic neuropathy, loss of neurogenic control of bone remodelling, increased osteoclast activity, osteolysis and progressive degeneration (Larson and Burns, )…”
Section: Unwanted Side Effectsmentioning
confidence: 99%
“…In addition to this, monocytes obtained from Charcot patients present reduced secretion of anti-inflammatory cytokines, and increased resistance to apoptosis (21, 42). This resistance provided mainly by IL-1β and TNFα causes the persistence of the abnormally intense and prolonged inflammatory response (3). Ndip et al reported that IL-8 and Granulocyte-Colony Stimulating Factor (GCSF) were inducing monocytes into an osteoclastic differentiation along with the RANKL/RANK pathway (41).…”
Section: Pathophysiologymentioning
confidence: 99%
“…A variety of causes are held responsible for triggering, amplifying, and converting the inflammatory processes which appears to be the major suspect at hand (3). Firm evidence was set forth that proinflammatory cytokines, especially the receptor activator of the nuclear factor-κB (RANK) ligand (RANKL) system is responsible for abnormally intense osteoclastogenesis (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation